Indigenous Management Research - Holtbrügge, Dirk (Management International Review, 2013)
• While the last years have witnessed a tremendous economic boom in many emerging markets around the world, the knowledge of management practices in these countries lags behind their growing relevance in the world economy. One reason for this is that concepts, such as guanxi, jugaad, ubuntu, and blat, are not adequately reflected by traditional Western management theories. • We call for more context-specific research and for drawing on indigenous thought in developing new theories that do not only help to better understand management practices in emerging markets, but contribute to global management knowledge as well. • Examples of indigenous management concepts are illustrated and adequate context-sensitive research methods, such as locally-meaningful constructs and measures, participatory research, storytelling, and visual ethnography, are discussed. Moreover, we provide an overview of current research and conclude with major implications for indigenous management research. © 2012 Springer Fachmedien Wiesbaden.
WiSo-Import:2015-03-26:3964
Keywords: Cross-cultural management; Emerging markets; Indigenous management; Research methods